2016
DOI: 10.1038/hr.2016.50
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodeling after reduction of high-flow arteriovenous fistulas in end-stage renal disease

Abstract: In patients with end-stage renal disease, excessive blood flow through an arteriovenous fistula (AVF) may lead to volume overload-induced cardiac remodeling and heart failure. It is unclear which patients with hyperfunctional AVF may benefit from AVF reduction or ligation. The indication for the procedure is often based on AVF flow. Because cardiac remodeling is driven by increased venous return, which is equivalent to cardiac output, we hypothesized that an elevated cardiac index (CI) might better identify su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…3b). The return flow has to be put in relation to the size of the patient and the total cardiac output [29]. The present case supports repeated routine measurement of pre-dialysis NT-proBNP as it may help to detect progressive cardiac strain better and relate it to AVF flow changes.…”
Section: Discussionsupporting
confidence: 59%
“…3b). The return flow has to be put in relation to the size of the patient and the total cardiac output [29]. The present case supports repeated routine measurement of pre-dialysis NT-proBNP as it may help to detect progressive cardiac strain better and relate it to AVF flow changes.…”
Section: Discussionsupporting
confidence: 59%
“…This high left-to-right shunt leads to cardiac volume overload, which in turn leads to high cardiac demand, cardiac hypertrophy and ultimately classical high output heart failure 39 . Ligation or reduction of AVF in patients with high-flow access may lead to reduction in left ventricular enddiastolic diameter 40 . Moreover, AVF is associated with pulmonary hypertension, a progressive and potentially fatal cardiopulmonary condition that is improved by ligation of AVF 41 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear what effect AVF reduction has on heart remodelling. In a published series of thirty patients with AVF fl ow ≥ 1.5 L/min treated by aneurysmorrhaphy with external mesh prosthesis, Wohlfahrt et al [35] evaluated the effect of reduction of AVF fl ow on cardiac remodelling. Reverse cardiac remodelling (decreased LV end-diastolic diameter and mass, left atrial and right ventricular diameter and pulmonary pressure) was observed only in patients with elevated cardiac index (≥ 3.9 L/min/ m 2 ).…”
Section: High Output Cardiac Failurementioning
confidence: 99%
“…While several studies have reported on the treatment of high fl ow vascular access, only a few of them assess high fl ow vascular access in the presence of an aneurysm. Aneurysmorrhaphy with external mesh can signifi cantly reduce fl ow rates [35,43] and precipitate reverse cardiac remodelling with fl ow rates ≥ 1.5 L/min in patients with elevated cardiac index (≥ 3.9 L/min/m 2 ) [35]. However, aneurysmorrhaphy has proven unsuccessful with fl ow rates >2.5 L/min [19].…”
Section: Surgical Techniques For High Fl Ow Avfamentioning
confidence: 99%